The Analysis of Students' Responses Toward The Computer-Based National Examination in Sciences Subject in Kabupaten Pasaman Barat - alfiyan resky; Arief Muttaqiin (Department of Science Education, 2020)
This study describes students responses to the material tested in the Computer-Based National Examinations in Sciences Junior High School in West Pasaman Regency. Data obtained from questionnaires distributed online to students who have conducted a computer-based national exam in 2019. The Computer-Based National Exam material for science subjects consists of 5 materials that will be categorized into materials that are considered easy and difficult for students. Research shows that material that is considered to be easy is sentient beings and their environment while material that is considered difficult is waves, electricity and magnetism.